Zein and luteolin composite material and modified material and preparation method thereof
By treating the composite system of zein and luteolin under high pressure fields, the problems of low stability and bioavailability are solved, and the thermal stability, solubility and antioxidant are improved.
Patent Information
- Application Number
- CN202310661777.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-06
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2043-06-06
AI Technical Summary
Zein and luteolin have problems with low stability and bioavailability in their applications, which affect their high-value utilization and biological activity.
By treating the zein and luteolin complex system under high pressure fields, a new complex is formed, which improves its thermal stability, solubility and antioxidant properties.
It improves the thermal stability and solubility of zein and luteolin composites, reduces surface hydrophobicity, enhances oxidation resistance, and improves its bioavailability.
Smart Images

Figure CN116769319B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of zein and luteolin composite materials, and in particular to a zein and luteolin composite material and a modified material and a preparation method thereof. Background Art
[0002] Corn is the largest grain crop in China, and its processed products are mainly used in various food, feed and fermentation industries. Zein is a plant protein separated from corn endosperm. Its amino acid composition is relatively special, containing a large number of hydrophobic amino acids and having amphiphilicity. It is mainly used in food and pharmaceutical fields such as nanoemulsions, embedding delivery, and drug sustained release. Luteolin (Lu) is a representative natural flavonoid (3′,4′,5,7-tetrahydroxyflavone), which is mainly found in various plants and has multiple biological activities, but it is sensitive to environmental factors such as temperature, pH, and light, has poor water solubility and stability, and low bioavailability. Summary of the invention
[0003] In order to improve the high-value utilization of zein and the bioavailability of luteolin, the present invention provides a zein and luteolin composite material and its modified material and preparation method. The method uses zein and luteolin as raw materials. Under high pressure field (high hydrostatic pressure or high pressure homogenization), the zein and luteolin composite system interact with each other to form a new composite, and the thermal stability and solubility of the composite are increased, the surface hydrophobicity is reduced, and the antioxidant property is increased.
[0004] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0005] The method for preparing a composite material of zein and luteolin of the present invention comprises the following steps:
[0006] According to the ratio, zein and luteolin are dissolved in an ethanol aqueous solution and mixed evenly to obtain a zein and luteolin composite material.
[0007] In the zein and luteolin composite material, the mass concentration of zein is 0.2-0.3 mg / mL; the molar concentration of luteolin is 20-50 μmol / L.
[0008] The mixing temperature is 20-45°C, preferably 20-25°C.
[0009] The zein and luteolin composite material is selected from a zein and luteolin composite liquid or a zein and luteolin composite solid; preferably a zein and luteolin composite solid material.
[0010] The zein and luteolin composite solid is obtained by dialyzing a zein and luteolin composite liquid to remove ethanol and then freeze-drying it.
[0011] The dialysis bag used in the dialysis is 3500Da, and the dialysis time is more than 12 hours.
[0012] In the preparation method of the zein and luteolin composite material, in the ethanol-water solution, the volume ratio of ethanol:water is (7-8):(2-3).
[0013] The zein and luteolin composite material of the invention is prepared by the above-mentioned preparation method, and has a solubility of 20-40%, a bromophenol blue binding amount of 81-82 μg, and a protein denaturation temperature of 116-119°C.
[0014] The method for preparing a composite material of modified zein and luteolin of the present invention comprises the following steps:
[0015] The zein and luteolin composite material is modified by adopting a high pressure field to obtain a modified zein and luteolin composite material.
[0016] Furthermore, the high pressure field is a high pressure homogenization treatment or a high hydrostatic pressure treatment.
[0017] The pressure of the high-pressure homogenization treatment is 20-100 MPa; the process of high hydrostatic pressure treatment is: placing the zein and luteolin composite solution in a vacuum high-pressure bag and treating it at 100-500 MPa for 5-20 minutes.
[0018] A composite material of modified zein and luteolin is prepared by the above preparation method. After high hydrostatic pressure treatment, it has a spherical structure, is evenly distributed at 300 MPa, and has a particle size of 3 to 4 μm. After high-pressure homogenization treatment, it has a spherical structure and micropores are generated on the surface, and the particle size is evenly 1.5 to 1.8 μm. After high hydrostatic pressure and high-pressure homogenization treatment, the molecular weight remains unchanged. After high hydrostatic pressure treatment, its solubility is 29.4% to 43.1%, and after high pressure homogenization treatment, its solubility is 30% to 70.3%. After high hydrostatic pressure treatment of 100 to 500 MPa, the r value (peak-to-valley ratio) of Zein is 0.450 to 0.615 respectively; after high pressure homogenization treatment of 20 to 100 MPa, the r value of Zein is 0.556 to 0.842. The r value (peak-to-valley ratio) calculated by the ultraviolet second-order derivative of Zein after treatment can also confirm the change in solubility; after high hydrostatic pressure treatment, the r value (peak-to-valley ratio) of Zein is 0.556 to 0.842. After treatment, the α-helix content was 39%-42%, and after high-pressure homogenization treatment, the α-helix content was 37-42%; after high hydrostatic pressure treatment, the bromophenol blue binding amount was 80-90μg, and after high-pressure homogenization treatment, the bromophenol blue binding amount was 85-89μg; after high hydrostatic pressure treatment, the decomposition temperature was 114℃-120℃, and after high-pressure homogenization treatment, the decomposition temperature was 94℃-119℃; after high hydrostatic pressure treatment, the DPPH free radical scavenging activity was 84%-90%, and after high-pressure homogenization treatment, the DPPH free radical scavenging activity was 83%-90%.
[0019] The beneficial effects of the present invention are:
[0020] (1) The composite material of zein and luteolin prepared by the present invention shows that the ultraviolet absorption of Zein increases with the increase of Lu concentration, and a red shift occurs at 209nm and a blue shift occurs at 278nm, which proves that Lu and Zein interact with each other. The double logarithmic curve analysis of the Zein-Lu composite system at different temperatures shows that there is at least one binding site in the Zein-Lu composite system, and the hydrophobic force is proved to be involved in the interaction between Lu and Zein by thermodynamic calculation. The circular dichroism spectrum shows that the addition of Lu makes the secondary structure of Zein orderly, and the non-covalent binding of the two promotes the transformation of the β-folding region and the random coil region to the α-helical region. The results of thermal stability also show that the addition of Lu can improve the thermal denaturation temperature of Zein. According to the results of fluorescence, infrared and molecular docking, Zein and Lu combine through hydrogen bonds and hydrophobic interaction forces, so that the protein structure aggregates and the thermal stability is enhanced. The results of surface hydrophobicity and solubility showed that the surface hydrophobicity and solubility of Zein were changed with the addition of Lu. Its hydrophilic hydroxyl and carboxyl groups reduced the surface hydrophobicity of Zein and enhanced the hydration of Zein, thereby increasing its solubility.
[0021] (2) The modified zein and luteolin composite materials were treated with high hydrostatic pressure and high pressure homogenization. The gel electrophoresis test results showed that the primary structure of Zein and Zein-Lu composite systems after different high pressure field treatments was not affected, but the scanning electron microscope observed that the changes in the microstructure of the two were different. Zein treated with high hydrostatic pressure reached the maximum aggregation state at 300MPa with the increase of pressure, while Zein treated with high pressure homogenization was evenly dispersed and micropores appeared on the surface. The Zein-Lu composite system was more compact and regular than Zein, and the high pressure homogenization treatment showed smaller spherical particles. The results of ultraviolet, fluorescence and synchronous spectroscopy experiments showed that different high pressure field treatments could change the tertiary structure of Zein. High pressure homogenization treatment with high hydrostatic pressure significantly changed the tertiary structure of Zein, and the fluorescence intensity continued to decrease with the increase of pressure. The aggregation degree of the Zein-Lu composite system was the highest at a high hydrostatic pressure of 300MPa. The ultraviolet absorption intensity of the Zein-Lu composite system under the treatment of two high pressure fields was higher than that of the untreated sample, indicating that the hydrogen bond and hydrophobic interaction between the two was greater than the effect of different pressure field treatment on its structure. At the same time, the synchronous fluorescence spectrum results showed that Zein and Zein-Lu composite systems moved near tryptophan under different high pressure field treatments. The circular dichroism test results showed that different high pressure field treatments changed the secondary structure of Zein and Zein-Lu composite systems, destroyed the arrangement of the hydrogen bond structure of the protein, and reduced the α-helix content. The effect of high pressure homogenization on the α-helix content of Zein was lower than that of high hydrostatic pressure. The α-helix content of the Zein-Lu composite system was still reduced after treatment, and the effect of high pressure homogenization was more significant, indicating that pressure treatment can also change the binding of Zein and Lu. The experimental results of surface hydrophobicity showed that the surface hydrophobicity of Zein and Zein-Lu composite systems after high hydrostatic pressure treatment first decreased and then increased with the increase of pressure, and continued to decrease after reaching the maximum at 300MPa. The surface hydrophobicity after high-pressure homogenization treatment continues to decrease, and this result can also be confirmed by calculating the ultraviolet second-order derivative of Zein under high-pressure field treatment. The solubility test results show that the effect of different high-pressure field treatments on the solubility of Zein alone is relatively small compared to Zein-Lu. High hydrostatic pressure treatment can further improve the solubility of Zein-Lu complex, and it decreases with the increase of pressure, reaching the lowest at 300MPa and the maximum at 500MPa, with an increase of 8%. The solubility of the Zein-Lu composite system after high-pressure homogenization treatment is significantly increased, reaching 70.3% under 100MPa treatment, an increase of 36%. The test results of thermal properties show that the thermal stability of Zein and Zein-Lu composite systems after high hydrostatic pressure treatment is the highest at 300MPa, while the thermal stability of high-pressure homogenization continues to increase with the increase of pressure.The test results of antioxidant properties show that the antioxidant properties of Zein and Zein-Lu composite systems were not weakened after treatment with different high pressure fields, and the antioxidant properties of the Zein-Lu composite system showed a synergistic effect in the high hydrostatic pressure and low pressure stages, and the same effect also appeared when the high pressure homogenization pressure increased. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The UV-visible absorption spectra of the zein and luteolin composite materials prepared in Comparative Examples 1-2 and Examples 1-4 of the present invention.
[0023] Figure 2 It is the Stern-Volmer curve of the Zein-Lu composite system at different temperatures of the present invention.
[0024] Figure 3 It is the double logarithmic curve of the Zein-Lu composite system at different temperatures of the present invention.
[0025] Figure 4 Circular dichroism spectra of Zein and Zein-Lu composite system with different concentrations of Lu in the present invention.
[0026] Figure 5 The DSC graphs of Zein of the present invention and Zein-Lu composite system with different concentrations of Lu are shown in FIG.
[0027] Figure 6 The surface hydrophobicity of Zein of the present invention and Zein-Lu composite system with different concentrations of Lu.
[0028] Figure 7 It is the solubility of Zein of the present invention and Zein-Lu composite system with different concentrations of Lu.
[0029] Figure 8 The UV-visible absorption spectra of Zein (A) after high-pressure microfluidization treatment of the present invention and the comparison of high-pressure homogenization treatment at 50 MPa (B).
[0030] Fig. 9 The Zein infrared spectra and secondary structure contents of the high-pressure microfluidization treatment of the present invention and the high-pressure homogenization treatment at 50 MPa are compared.
[0031] Fig.10 (A) is the SDS-PAGE of Zein and Zein-Lu after high hydrostatic pressure treatment of the present invention; (B) is the SDS-PAGE of Zein and Zein-Lu after high-pressure homogenization pressure treatment of the present invention.
[0032] Fig.11The ultraviolet spectra of Zein (A), (B) and Zein-Lu composite system (C), (D) after high hydrostatic pressure and high pressure homogenization treatment of the present invention.
[0033] Fig.12 The fluorescence spectra of Zein (A), (B) and Zein-Lu composite system (C), (D) after high hydrostatic pressure and high pressure homogenization treatment of the present invention.
[0034] Fig.13 Circular dichroism spectra of Zein (A), (B) and Zein-Lu composite system (C), (D) after high hydrostatic pressure and high pressure homogenization treatment of the present invention.
[0035] Fig.14 Scanning electron micrographs of Zein (A), (B) and Zein-Lu composite systems (C), (D) after high hydrostatic pressure and high pressure homogenization treatment of the present invention.
[0036] Fig.15 The surface hydrophobicity of Zein and Zein-Lu composite system before high hydrostatic pressure (A) and high pressure homogenization (B) treatment of the present invention.
[0037] Fig.16 The solubility of Zein and Zein-Lu composite system after high hydrostatic pressure (A) and high pressure homogenization (B) treatment of the present invention.
[0038] Fig.17 The second derivative ultraviolet spectra of Zein after high hydrostatic pressure (A) and high pressure homogenization (B) treatments of the present invention.
[0039] Fig.18 DSC graphs of Zein (A), (B) and Zein-Lu composite system (C), (D) after high hydrostatic pressure and high pressure homogenization treatment of the present invention.
[0040] Fig.19 The antioxidant properties of Zein (A), (B) and Zein-Lu composite system (C), (D) after high hydrostatic pressure and high pressure homogenization treatment of the present invention. DETAILED DESCRIPTION
[0041] The present invention is further described in detail below in conjunction with embodiments.
[0042] In the following examples, unless otherwise specified, the raw materials used were commercially available and the test methods used were conventional test methods.
[0043] In the following examples, Fourier transform infrared spectroscopy was tested using a tablet pressing method.
[0044] In the following examples, the thermal properties of the zein and luteolin composite materials were measured by differential scanning calorimetry.
[0045] In the following examples, the surface hydrophobicity of the zein and luteolin composite material was determined using the bromophenol blue method.
[0046] Comparative Example 1
[0047] The zein is directly added into the ethanol aqueous solution with a volume concentration of 70% / 30%.
[0048] Comparative Example 2
[0049] A 0.1 mg / mL luteolin ethanol aqueous solution and a 0.2-0.3 mg / mL zein ethanol aqueous solution were mixed at a molar ratio of 10 μmol / L luteolin to obtain a zein and luteolin composite material, which was prepared into a corresponding liquid or solid according to the test requirements.
[0050] Examples 1-4
[0051] A 0.1 mg / mL luteolin ethanol aqueous solution and a 0.2-0.3 mg / mL zein ethanol aqueous solution were mixed at different gradient molar ratios of luteolin (20, 30, 40, 50 μmol / L) to obtain a zein and luteolin composite material, which was prepared into corresponding liquid or solid according to the test requirements.
[0052] Detection of corresponding liquids or solids:
[0053] By ultraviolet spectroscopy ( Figure 1 ) confirmed that Zein and Lu formed a complex and interacted with each other.
[0054] Figure 2 The Stem-Volmer curves of Lu fluorescence quenching on Zein at three different temperatures show a good linear relationship at all three temperatures (R 2 =0.971, 0.976, 0.989), and the linear Stem-Volmer curve shows that there is only one quenching mechanism when Zein and Lu are quenched.
[0055] Table 1 Fluorescence quenching parameters of Zein-Lu interaction at different temperatures
[0056]
[0057] Table 1 reflects the fluorescence quenching parameters of Zein-Lu interaction at different temperatures. It can be seen from the table that with the increase of temperature, the quenching constant K of the composite system SV The stability of the ground state complex is significantly reduced, and the increase in temperature can increase the effective collision between molecules. At the same time, the Kq The values are much larger than the maximum collision quenching constant (2×10 10 L / mol·s). Therefore, it can be concluded that the static quenching mechanism dominates the fluorescence quenching process of the composite system. There is at least one binding site between the two, and the binding ability decreases with the increase of temperature (25℃, 35℃, 45℃).
[0058] Table 2 Binding site number n and binding constant K of Zein-Lu composite system at different temperatures a and the linear correlation coefficient
[0059]
[0060] The binding constant and the number of Lu binding sites on Zein were calculated by fitting a double logarithmic curve. Figure 3 The three curves fitted in the experiment are summarized in Table 2. The K a All greater than 10 4 , indicating that there is a strong interaction between Lu and Zein. At the same time, with the increase of temperature, K a It can be seen from the table that the number of binding sites between Zein and Lu is greater than 1, and the n value is close to 1.5 at 25°C, indicating that when Lu and Zein interact, there is a primary binding site and a secondary binding site may appear at the same time. The correlation coefficients (R 2 ) are all greater than 0.98, indicating that the mathematical model is feasible for studying the interaction mechanism between Lu and Zein.
[0061] Table 3 Thermodynamic parameters of Zein-Lu at different temperatures
[0062]
[0063] The relevant parameters calculated by the Van't Hoff equation and the Gibbs free energy formula are summarized in Table 3. The positive and negative values of the thermodynamic parameter ΔG can represent whether the reaction is spontaneous. From the table, we know that ΔG is a negative value, indicating that the binding of the Zein-Lu composite system is spontaneous. When both the entropy change (ΔS) and the enthalpy change (ΔH) are greater than 0, it is a hydrophobic interaction; when both are less than 0, it is a hydrogen bond interaction; when the entropy change is greater than 0 and the enthalpy change is less than 0, it is an electrostatic interaction. In this study, ΔS (109.781 J / mol·K) and ΔH (133.830 kJ / mol) are both positive, indicating that the main interaction between Zein and Lu is hydrophobic interaction, and the binding process is an entropy-driven reaction.
[0064] The interaction between Zein and Lu can affect the secondary structure of proteins, as shown by circular dichroism ( Figure 4) showed that with the increase of Lu concentration, the α-helix content increased. The thermal stability and solubility of Zein also increased significantly, and the surface hydrophobicity decreased.
[0065] like Figure 5 The DSC graphs of Zein and Zein-Lu composite systems with different concentrations of Lu, Tp is the denaturation temperature of the protein, which is usually related to the breaking of hydrogen bonds. Tp reflects the changes in the denaturation temperature of the composite system with the increase of luteolin concentration. The thermal denaturation curve of Zein is concave, showing an exothermic effect, and Tp is 113.08±0.53°C (Comparative Example 1). When Zein and Lu form a composite system, the peak area of the thermal denaturation curve increases, the peak shape does not change significantly, and Tp tends to increase as a whole (Comparative Example 2 decreases, and Examples 1-4 all increase), which is due to the non-covalent binding of Zein and Lu. In addition, the fluorescence spectrum results show that hydrogen bonds are formed between Zein and Lu, which also explains the increase in thermal stability of the Zein-Lu composite system.
[0066] Bromophenol blue can bind to the hydrophobic sites of proteins with low water solubility. The hydrophobicity of the protein is positively correlated with the amount of bromophenol blue bound. Figure 6 It can be seen that the addition of Lu reduces the hydrophobicity of Zein. The main reason for this phenomenon may be that luteolin is embedded in the hydrophobic region of the protein, interacts with hydrophobic amino acids (such as proline), and introduces hydrophilic hydroxyl and carboxyl groups of luteolin, which reduces the hydrophobicity.
[0067] The solubility of Zein in water is low. In order to further explore the effect of Lu on the physical and chemical properties of Zein, the solubility of Zein in water after adding Lu was studied. Figure 7 As shown in the figure, with the addition of Lu, the solubility of Zein gradually increased, which may be due to the introduction of Lu's hydroxyl group, which enhanced the hydration of the protein. The addition of Lu significantly reduced the surface hydrophobicity of Zein and increased the surface charge, which increased the solubility.
[0068] Comparative Example 3
[0069] The composite solution of zein and luteolin was treated by high-pressure microfluidization at 50 MPa. A portion of the treated sample was stored at 4°C for subsequent liquid testing, and a portion was rotary evaporated to remove ethanol and freeze-dried for solid testing.
[0070] Embodiment 5-8
[0071] Zein was dissolved in 70% (v / v) ethanol aqueous solution to prepare an 8% (w / v) sample solution, and magnetically stirred at 25°C for 6 hours to completely dissolve the protein. A certain amount of Lu and Zein were weighed and dissolved in 70% (v / v) ethanol aqueous solution, mixed at room temperature to form a composite solution with a Zein concentration of 2 mg / mL and a Lu concentration of 50 μM, and magnetically stirred at room temperature for 6 hours to fully mix the two. Untreated Zein and the prepared zein and luteolin composite solution were homogenized three times at 20MPa, 50MPa, 80MPa and 100MPa pressures. A portion of the treated samples was stored at 4°C for subsequent liquid testing, and a portion was rotary evaporated to remove ethanol and freeze-dried for later use.
[0072] Examples 9-13
[0073] Zein was dissolved in 70% (v / v) ethanol aqueous solution to prepare an 8% (w / v) sample solution, and magnetically stirred at 25°C for 6 hours to completely dissolve the protein. A certain amount of Lu and Zein were weighed and dissolved in 70% (v / v) ethanol aqueous solution, mixed at room temperature to form a composite solution with a Zein concentration of 2 mg / mL and a Lu concentration of 50 μM, and magnetically stirred at room temperature for 6 hours to fully mix the two. Untreated Zein and the prepared zein and luteolin composite solution were placed in a polyethylene vacuum high-pressure bag and sealed using a vacuum packaging machine. The sealed sample was placed in the cavity of a high hydrostatic pressure device at room temperature and treated at 100, 200, 300, 400 and 500 MPa pressures for 10 minutes. Untreated Zein and Zein-Lu composite solutions were used as controls. Part of the treated samples were stored at 4°C for subsequent liquid testing, and part was rotary evaporated to remove ethanol and freeze-dried for standby use.
[0074] Analysis of Comparative Example 3 and Examples 5-13
[0075] (1) Ultraviolet spectrum analysis
[0076] like Figure 8 (A) shows the UV absorption spectrum of Zein after being treated with high-pressure microfluidics at 10-50 MPa. The characteristic absorption peaks of Zein are shown at 209 nm and 280 nm. As the pressure increases, the UV absorption intensity of Zein does not change much, indicating that the treatment with high-pressure microfluidics at 10-50 MPa has no significant effect on the tertiary structure of Zein, and the surrounding environment of the amino acid residues of Zein is not changed within this pressure range. Figure 8(B) shows the UV absorption spectrum comparison of Zein after high-pressure homogenization and high-pressure microfluidization treatment at 50MPa. It can be seen from the figure that the UV absorption intensity of Zein after high-pressure homogenization at 50MPa is significantly reduced, indicating that the turbulence generated by high-pressure homogenization promotes high-speed collisions between molecules, resulting in changes in the microenvironment of Zein tyrosine and tryptophan residues, and the amino acid residues move to the hydrophilic environment. This change also shows that high-pressure homogenization can better enhance the solubility of Zein.
[0077] (2) Infrared spectroscopy analysis
[0078] like Fig. 9 (A) shows the infrared spectrum of Zein treated with high-pressure microjet at 10-50 MPa. When Zein is treated with high-pressure microjet, the infrared spectrum at 3319 cm -1 The absorption peak at blue shifted to 3311 cm -1 This indicates that high pressure microfluidization treatment promotes the formation of hydrogen bonds. -1 and 1535cm -1 The absorption peak shifted to 1656 cm -1 and 1537cm -1 It shows that the stretching vibrations of C=O, CN and NH are enhanced after high-pressure microfluidization treatment, but the stretching vibrations of amide A with OH, as well as amide I and amide II regions, do not change with the increase of pressure. Fig. 9 (B) shows the infrared spectra comparison of high-pressure microfluidization and high-pressure homogenization under 50MPa treatment. Compared with high-pressure homogenization, high-pressure microfluidization can slightly change the stretching vibration of functional groups.
[0079] Amide I bands are often used to analyze the secondary structure of proteins. Fig. 9 (C) and (D) show the secondary structure content of Zein after high-pressure microfluidization treatment and high-pressure homogenization treatment. It can be seen from the figure that the relative content of α-helix and β-fold of Zein after high-pressure microfluidization treatment shows a downward trend, and the relative content of β-turn shows an increasing trend. This shows that the disorder of Zein is increased after high-pressure microfluidization treatment, causing it to unfold. The reduction of β-fold content promotes its structural unfolding, which leads to an increase in its flexibility. The reduction of hydrogen bonding plays a dominant role in the change of its secondary structure. However, with the increase of pressure, the secondary structure content does not change, indicating that the secondary structure of Zein is not significantly affected within the treatment range of 50MPa. The relative content of α-helix of Zein treated with 50MPa high-pressure homogenization is slightly lower than that of Zein treated with high-pressure microfluidization, indicating that high-pressure homogenization treatment makes it unfold more thoroughly and more flexible. This may be due to the participation of mechanical forces of shear and high-speed impact, which induces the dissociation of some protein aggregates.
[0080] Compared with high-pressure microfluidization, high-pressure homogenization can better modify the secondary structure of Zein and improve the solubility of Zein.
[0081] (3) Gel electrophoresis analysis
[0082] Gel electrophoresis (SDS-PAGE) can analyze the molecular weight distribution of proteins and reflect the changes in protein subunit structure and aggregation state. Fig.10 The SDS-PAGE diagram of Zein and Zein-Lu complex system under different high pressure field pressure treatment is shown. It can be seen from the figure that zein has two obvious bands near 20-25kDa and 50kDa. The band in the range of 20-25kDa represents the α-zein subunit, which occupies 70%-85% of zein, and the band of 50kDa is mainly the γ-zein subunit, which occupies 10%-20% of zein. No extra bands are produced in the figure, indicating that different high pressure field pressure treatments and the addition of Lu will not destroy the primary structure of Zein, and cannot decompose the protein into smaller molecular weight polypeptides or larger molecular weight proteins. Among them, the samples of Zein and Zein-Lu complex system treated with high hydrostatic pressure move towards the low molecular weight direction compared with the α-Zein band of the high pressure homogenization treated sample, which indicates that the molecular weight and aggregation degree of α-Zein of Zein and Zein-Lu complex system treated with high hydrostatic pressure are slightly reduced.
[0083] (4) Analysis of UV spectrum
[0084] like Fig.11The figure shows the UV absorption spectra of Zein and Zein-Lu composite system under different high pressure field pressure treatment. Figures (A) and (B) are the UV absorption spectra of Zein before and after high hydrostatic pressure and high pressure homogenization pressure treatment. It can provide information on the tertiary structure of Zein before and after treatment, which is used to evaluate the chromophore (aromatic amino acid residue) and monitor the changes in protein conformation. As can be seen from the figure, Zein shows an absorption peak of tyrosine residues at 278nm. With the addition of pressure, the UV absorption spectrum of Zein after treatment has no obvious red shift or blue shift, but compared with the control Zein, the UV absorption intensity of Zein treated with high hydrostatic pressure and high pressure homogenization shows an overall decreasing trend. This may be due to the vibration of tryptophan and tyrosine residues, the burial of hydrophobic groups and changes in secondary structure modification. It is worth noting that the UV spectrum shows different trends in different treatments. After high hydrostatic pressure treatment, the UV absorption intensity shows a trend of first increasing and then decreasing with the increase of pressure, and gradually decreases with the increase of pressure after reaching the maximum value at 300MPa. This shows that under the treatment of high hydrostatic pressure and different pressures, the structure of Zein has changed to varying degrees with the change of pressure. For Zein treated with high-pressure homogenization, the absorbance of Zein continues to decrease with the increase of pressure, which may be due to the turbulence of high-pressure homogenization promoting high-speed collisions between molecules.
[0085] Fig.11 (C) and (D) are the UV absorption spectra of the Zein-Lu composite system before and after different high pressure field treatments. It can be seen from the figure that the overall absorption intensity of the Zein-Lu composite system increases after different high pressure field treatments, which is different from the trend of treating Zein alone, and the maximum value is reached at 300MPa for high hydrostatic pressure and 50MPa for high pressure homogenization. Zein and Lu are non-covalently complexed through hydrogen bonds and hydrophobic interactions. The addition of Lu affects the spatial conformation of the protein and unfolds the structure of the protein. The interaction force between the two is greater than the influence of the high pressure field. The change in the UV absorption intensity of ZeIn-Lu after high pressure homogenization is more significant than that after high hydrostatic pressure treatment. The interaction between Zein and Lu is strongest under high pressure homogenization at 50MPa.
[0086] (5) Analysis of fluorescence spectra
[0087] Since proteins contain amino acid residues such as tryptophan (Trp), tyrosine (Tyr) and phenylalanine (Phe), they are highly sensitive to the polarity of the microenvironment. Therefore, when the excitation wavelength is set to 280nm, the tertiary structure changes of proteins can be determined by fluorescence fluctuations (fluorescence shift or quenching reaction). Since the Tyr content in Zein is high and Trp is significantly missing, the strong fluorescence peak of zein near 304nm is mainly contributed by Tyr residues. Fig.12 (A) and (B) are the fluorescence spectra of Zein before and after treatment with high hydrostatic pressure and high pressure homogenization. The fluorescence intensity of Zein after treatment with different high pressure fields showed a downward trend, which indicates that applying a certain pressure to Zein will destroy the structure of Zein, causing the protein structure to fold, and most of the hydrophobic groups to be buried, resulting in a decrease in fluorescence intensity. The changes of Zein after high pressure homogenization treatment are significant compared with those after high hydrostatic pressure treatment. With the increase of high pressure homogenization treatment pressure, the fluorescence intensity of Zein shows a continuous decline. At the same time, it can be seen from the figure that the fluorescence absorption peak of Zein after pressure field treatment is observed to be the maximum at about 305nm, resulting in a slight red shift. These results indicate that the microenvironment of Tyr has changed and moved to the hydrophilic area, resulting in a weakening of hydrophobicity.
[0088] With the addition of Lu, Fig.12 As shown in (C) and (D), the fluorescence intensity of the composite system showed a downward trend, indicating that Zein and Lu interacted, and the interaction significantly quenched the fluorescence of Zein. At the same time, the composite system treated with high pressure field was lower than that of the untreated one. This is because the Zein-Lu composite system promoted the interaction between Zein and Lu after being treated with high pressure field, and the aromatic amino acids exposed by Zein were buried again, resulting in a decrease in fluorescence intensity. The Zein-Lu composite system treated with high pressure homogenization has the same effect as high hydrostatic pressure, and the fluorescence intensity is lower than that of the untreated composite system. However, the fluorescence intensity of the composite system treated with high hydrostatic pressure gradually increases with the increase of pressure, reaching the highest point at 300MPa, and gradually decreases with the continued increase of pressure. This trend is consistent with the results of ultraviolet spectrum. This phenomenon also shows that the interaction between Zein and Lu treated with high hydrostatic pressure is the weakest at 300MPa. The fluorescence intensity of the composite system treated with high pressure homogenization gradually decreases with the increase of pressure, reaching the lowest at 80MPa, and increases at 100MPa.
[0089] (6) Analysis of circular dichroism
[0090] Fig.13The circular dichroism spectra of Zein and Zein-Lu before and after treatment with high hydrostatic pressure and high pressure homogenization. In far-ultraviolet circular dichroism, the average residual ellipticity at 208nm generally indicates the content of α-helix, while the amplitude of the chromatographic curve indicates the increase or decrease of the content. From Figures A and B, it can be seen that the absorption peak of Zein at 208nm before and after high hydrostatic pressure treatment is higher than that of untreated Zein. However, the absorption peak at this wavelength did not change significantly after high pressure homogenization treatment. This indicates that after high hydrostatic pressure treatment, the protein system with α-helix as the main conformation began to change to other conformations, and the conformation of Zein began to become disordered. Calculations show that the α-helix structure content of natural Zein is 45.20%, and the α-helix content of Zein after high hydrostatic pressure treatment is 41.44%, 42.23%, 44.91%, 41.26% and 42.17%, respectively. This indicates that high hydrostatic pressure treatment will destroy the secondary structure of Zein and change the arrangement of hydrogen bonds in the protein conformation, thereby affecting the spatial conformation that maintains the helical structure. Fig.13 (B) shows the changes in the secondary structure of Zein before and after high-pressure homogenization. Calculations show that the α-helix content of Zein after high-pressure homogenization is 44.24%, 45.23%, 45.11%, and 45.62%, respectively, indicating that Zein maintains its original α-helix structure content during the high-pressure homogenization and low-pressure stage.
[0091] like Fig.13 As shown in Figures C and D, after the Zein-Lu composite system was treated with high hydrostatic pressure and high-pressure homogenization, its α-helix characteristic absorption peak at 208nm moved upward with the increase of pressure. The α-helix content of Zein combined with Lu was calculated to be 50.50%, and its α-helix content after high hydrostatic pressure treatment was: 39.84%, 39.77%, 42.32%, 40.04% and 39.67%. The α-helix content after high-pressure homogenization treatment was: 42.56%, 39.64%, 37.42% and 38.34%. It shows that the secondary structure of Zein-Lu gradually unfolds Zein under high pressure field, changing from tight to loose. Therefore, it can be proved that pressure-induced structural changes may involve conformational rearrangement and exposure of certain groups in proteins, thereby improving the binding of proteins with other small molecules.
[0092] (7) Scanning electron microscopy analysis
[0093] Scanning electron microscopy was used to study the effects of different high pressure field treatments on the micromorphology of Zein and Zein-Lu composite systems. Fig.14A and B are Zein images at a magnification of 5000 times after high hydrostatic pressure and high pressure homogenization treatment, respectively. It can be seen from Figure A that the untreated Zein is a blocky sphere with a rough surface. After high hydrostatic pressure treatment, Zein shows an increased, aggregated spherical structure, which may be caused by the reduction of protein surface charge and the increase of electrostatic interaction between particles. The aggregation phenomenon is most obvious at 300MPa. When the pressure further rises to 500MPa, the pressure effect intensifies, and the cross-linked aggregates gradually dissociate. The scanning electron microscope image of the Zein sample under high pressure homogenization treatment is shown in Figure B. It can be seen that after high pressure and shear force treatment, Zein is a spherical shape of uniform size, the molecules aggregate to form more blocky micelles, and micropores are generated on the spherical surface. After treatment, the spherical dense structure of Zein is destroyed by shear force, impact force and cavitation, causing the protein structure to shrink and form irregular agglomerates. Figures C and D are Zein-Lu images under high hydrostatic pressure and high pressure homogenization treatment. After combining with Lu, the composite system showed a compact and regular spherical spatial structure. After high hydrostatic pressure treatment, its structure was observed to be more compact. This may be because the high pressure treatment destroyed the interaction between protein molecules and promoted more hydrophobic groups in Zein to be exposed to the surrounding environment and combined with Lu molecules. After the Zein-Lu composite system was treated with high-pressure homogenization, the protein particles were destroyed by shear force to obtain smaller particles, and the distribution was more uniform. As the pressure increased, the shear force increased, the spherical shape of the composite system became smaller and tended to aggregate.
[0094] (8) Analysis of surface hydrophobicity
[0095] Surface hydrophobicity is an important indicator for evaluating protein structural changes and interactions. We used the bromophenol blue method to analyze the changes in surface hydrophobicity of Zein and Zein-Lu before and after treatment with different high pressure fields. Fig.15(A) shows the surface hydrophobicity of Zein and Zein-Lu composite system before and after treatment with high hydrostatic pressure. The amount of bromophenol blue binding to Zein treated with 100MPa high pressure is the lowest, that is, the surface hydrophobicity is the lowest. With the increase of treatment pressure, the surface hydrophobicity increases, reaches the highest at 300MPa and then continues to decrease, but the surface hydrophobicity of all pressure-treated Zein is lower than that of untreated Zein. The surface hydrophobicity of the treated Zein-Lu composite system shows a trend of first increasing and then decreasing with the treatment pressure. Similarly, the surface hydrophobicity is the highest when treated with 300MPa and the lowest when treated with 500MPa. It is not difficult to find that the surface hydrophobicity of Zein and Zein-Lu composite system before and after high hydrostatic pressure treatment has the same trend as the corresponding fluorescence intensity. With the increase of treatment pressure, the protein initially unfolds under medium pressure, the hydrophobic groups decompose at this stage, the surface hydrophobicity increases, and then the protein rebinds and aggregates under higher pressure. Lu non-covalently binds to Zein through hydrophobic interaction, which reduces the overall binding of bromophenol blue to Zein. The surface hydrophobicity is lower than that of Zein alone, and the surface hydrophobicity changes with the continuous change of treatment pressure. The results of high-pressure homogenization and high hydrostatic pressure are different. The aggregation of proteins after high-pressure homogenization is reflected in the reduction of surface hydrophobicity. This may be due to the laminar flow effect during the high-pressure homogenization process. The protein dispersed phase droplets are sheared and stretched, and the aggregation of unfolded proteins leads to the formation of protein aggregates with large molecular weight. The hydrophilic and hydrophobic groups are buried, and the surface hydrophobicity is subsequently reduced.
[0096] (9) Analysis of solubility
[0097] Solubility is the most practical measure of the extent of protein denaturation and aggregation and is therefore a good indicator of protein functionality. Fig.16The solubility of Zein and Zein-Lu composite system before and after high hydrostatic pressure (A) and high pressure homogenization (B) treatment. It can be seen from the figure that the addition of Lu can significantly improve the solubility of Zein, which is attributed to the hydrogen bond and hydrophobic interaction between Lu and Zein, and the hydrophobicity of the protein decreases. Overall, the solubility of Zein and Zein-Lu composite system treated with high hydrostatic pressure shows a trend of first decreasing and then increasing with the increase of high hydrostatic pressure. When the pressure is 300MPa, the solubility of Zein-Lu reaches the minimum value (29.42%), and reaches the maximum value (43.07%) under the treatment of 500MPa, which may be due to the high binding of Zein-Lu under this pressure. This shows that high hydrostatic pressure treatment under high pressure can further increase the solubility of Zein and Zein-Lu complexes. The solubility of Zein and Zein-Lu composite system after high pressure homogenization treatment is significantly increased, reaching a maximum of 70.3% under 100MPa treatment. This may be because the composite system is affected by cavitation, which causes small bubbles in the solution to burst rapidly under high pressure, releasing energy and causing local solution shock and fluctuations, destroying the disulfide bonds inside the protein, causing the protein molecules to unfold, reducing the molecular volume, and expanding the contact area with water, thereby increasing solubility. On the other hand, the interaction ability of protein with water is improved after denaturation, so the solubility of the complex is improved.
[0098] (10) Ultraviolet second-order derivative analysis
[0099] The structures of Zein and Zein-Lu were characterized by UV spectrum. In the UV spectrum, the absorption peak near 280nm is mainly attributed to the absorption of tryptophan and tyrosine. Fig.17Figures A and B show the second-order derivative UV spectra of Zein under high hydrostatic pressure and high-pressure homogenization treatment. The microenvironmental changes of tyrosine and tryptophan residues were analyzed by second-order derivative fitting. This calculation is more suitable for the calculation of single proteins after high-pressure treatment. Before and after treatment, Zein showed two positive absorption peaks and a negative absorption peak in the range of 280-300nm. The conformational changes of tyrosine residues can be inferred by calculating the ratio of the two peak-to-valley values marked in the figure (r=a / b). The ratio of the peak-to-valley values and the position of the peak-to-valley in the second-order derivative spectrum of the protein are functions of the relative amounts of the two amino acids and the average polarity of the protein. The r value of Zein before high hydrostatic pressure treatment was 0.537, and the r values of Zein after treatment with high hydrostatic pressure of 100-500MPa were 0.615, 0.578, 0.450, 0.556 and 0.529, respectively. When the pressure increases from 100MPa to 500MPa, the average polarity of tyrosine increases as a whole, that is, the hydrophobicity decreases as a whole. And only at 300MPa does the average polarity of tyrosine decrease and the hydrophobicity increase slightly. This trend is consistent with the change trend of Zein solubility after high hydrostatic pressure treatment. The r values of Zein after high pressure homogenization at pressures of 20 to 100MPa are 0.556, 0.842, 0.666, and 0.600, respectively. The average polarity of tyrosine increases and the hydrophobicity decreases.
[0100] (11) Analysis of thermal characteristics
[0101] The thermal properties of proteins can be identified by differential scanning calorimetry (DSC), which measures the thermal denaturation of proteins during constant heating and provides information related to the thermal stability of proteins, namely the denaturation temperature (T d ). d Reflects the temperature required for protein denaturation. Fig.18 A and B are the DSC curves of Zein after high hydrostatic pressure and high pressure homogenization. From Table 4, we know that with the increase of high hydrostatic pressure, the T d The temperature shifts to higher temperatures, as shown by the T of the untreated Zein. d The temperature of Zein increases from 113.08℃ to 119.33℃ at 300MPa. At the same time, it reaches the highest value at 300MPa. As the pressure continues to increase, the thermal stability of Zein gradually decreases. This shows that under the action of high hydrostatic pressure, Zein gradually expands with the increase of pressure, the structure becomes loose and more disordered, and the thermal stability gradually decreases. The T of Zein after high pressure homogenization treatment is d The temperature of Zein increased continuously from 113.08℃ to 123.62℃ with the increase of pressure, which indicates that the high-pressure homogenization treatment changed the spatial conformation of Zein.
[0102] Fig.18Figures C and D are DSC curves of Zein-Lu after high hydrostatic pressure and high pressure homogenization treatment. With the addition of Lu, the denaturation temperature of the composite system increased. The composite system under high hydrostatic pressure treatment also reached the highest value at 300MPa. High hydrostatic pressure treatment can lead to incomplete or complete unfolding of proteins, and may also cause protein re-aggregation, but the thermal stability of Zein-Lu in the composite system increases at higher pressures. This shows that high hydrostatic pressure promotes the interaction between the two at higher pressures for the Zein-Lu composite system, causing the composite system to aggregate and enhance thermal stability. Similarly, in the Zein-Lu composite system treated with high pressure homogenization, the interaction between the two is destroyed in the low pressure stage, resulting in a decrease in thermal stability. As the pressure increases, the aggregation of the two is also promoted, thereby improving thermal stability.
[0103] Table 4 DSC thermodynamic parameters of Zein and Zein-Lu composite system after high hydrostatic pressure and high pressure homogenization treatment
[0104]
[0105] (12) Analysis of Antioxidant Properties
[0106] As we all know, Lu has good antioxidant activity, and whether the antioxidant activity of Lu will change after it is combined with Zein, and how different high-pressure field treatments will affect the antioxidant activity of the complex has attracted our attention. In recent years, a variety of methods have emerged to determine the antioxidant capacity of food. We selected DPPH and ABTS methods to comprehensively examine the changes in the antioxidant activity of Zein and Zein-Lu complexes.
[0107] DPPH is a stable free radical that has a single electron and can accept an electron or hydrogen ion, so it is widely used to evaluate the antioxidant activity of substances. Fig.19 It can be seen from (A) and (B) that the DPPH and ABTS free radical scavenging ability of Zein after being treated with different high pressure fields shows different trends compared with the untreated Zein. The Zein treated with high hydrostatic pressure is higher than the untreated Zein. The DPPH scavenging ability decreases with the increase of pressure, indicating that the pressure treatment promotes the changes between protein molecules, making it exert a stronger antioxidant effect. It shows the lowest antioxidant activity at 300MPa. The antioxidant effect of Zein treated with high-pressure homogenization shows a slight downward trend after the pressure increases. This result shows that high-pressure field treatment can affect the antioxidant activity of Zein, but attention should be paid to the range of pressure treatment. Fig.19It can be seen from (C) and (D) that the antioxidant activity of Zein and Lu is significantly increased after the composite. The high pressure field treatment can promote the interaction between Zein and Lu. The Zein-Lu composite system treated with high hydrostatic pressure in the low pressure stage has a synergistic antioxidant effect. The composite system treated with high pressure homogenization also has significantly increased antioxidant activity under high pressure field treatment. This shows that appropriate high pressure field treatment can improve the antioxidant activity of Zein and Zein-Lu composite system.
Claims
1. A composite material of zein and luteolin, characterized in that: Mixing zein and luteolin; The zein and luteolin composite material is prepared by the following preparation method: According to the ratio, zein and luteolin are dissolved in an ethanol aqueous solution, and mixed evenly to obtain a zein and luteolin composite material; In the zein and luteolin composite material, the mass concentration of zein is 0.2-0.3 mg / mL; and the molar concentration of luteolin is 20-50 μmol / L.
2. The zein and luteolin composite material according to claim 1, characterized in that: The solubility of the zein and luteolin composite material is 20-40%, the bromophenol blue binding amount is 81-82 μg, and the denaturation temperature of the protein is 116-119°C.
3. The method for preparing the composite material of zein and luteolin according to claim 1 or 2, characterized in that: The following steps are involved: According to the ratio, zein and luteolin are dissolved in an ethanol aqueous solution and mixed evenly to obtain a zein and luteolin composite material.
4. The method for preparing the composite material of zein and luteolin according to claim 3, characterized in that: In the zein and luteolin composite material, the mass concentration of zein is 0.2-0.3 mg / mL; the molar concentration of luteolin is 20-50 μmol / L.
5. The method for preparing the composite material of zein and luteolin according to claim 3, characterized in that: The mixing temperature is 20-45° C.; and / or, in the ethanol-water solution, the volume ratio of ethanol:water is (7-8):(2-3).
6. A method for preparing a composite material of modified zein and luteolin, characterized in that: The following steps are involved: The zein and luteolin composite material according to claim 1 or 2 is modified by using a high pressure field to obtain a modified zein and luteolin composite material; The high pressure field is a high pressure homogenization process or a high hydrostatic pressure process; The pressure of the high-pressure homogenization treatment is 20-100 MPa; the process of the high hydrostatic pressure treatment is: placing the zein and luteolin composite solution in a vacuum high-pressure bag and treating it at 100-500 MPa for 5-20 minutes.
7. A composite material of modified zein and luteolin, characterized in that: The method according to claim 6 is used to prepare the product.
8. The modified zein and luteolin composite material according to claim 7, characterized in that: When the high pressure field is high hydrostatic pressure treatment, the modified zein and luteolin composite material is a spherical structure, which is relatively evenly distributed at 300MPa, with a particle size of 3-4μm; the solubility is 29.4%-43.1%, and the ratio of the r value peak to valley value of Zein after treatment with high hydrostatic pressure of 100-500MPa is 0.450-0.615; the α-helix content is 39%-42%, the bromophenol blue binding amount is 80-90μg, the decomposition temperature is 114℃-120℃, and the DPPH free radical scavenging activity is 84%-90%.
9. The modified zein and luteolin composite material according to claim 7, characterized in that: When the high pressure field is high pressure homogenization treatment, the modified zein and luteolin composite material is a spherical structure with micropores on the surface, the particle size is uniformly 1.5-1.8 μm, the solubility is 30%-70.3%, and after high pressure homogenization treatment at a pressure of 20-100 MPa, the r value of Zein is 0.556-0.842, the α-helix content is 37-42%, the bromophenol blue binding amount is 85-89 μg, the decomposition temperature is 94°C-119°C, and the DPPH free radical scavenging activity is 83%-90%.
Citation Information
Patent Citations
Composite condensation product with double-embedding function as well as preparation method and application of composite condensation product
CN112205628A
Zein-polyphenol covalent complex and preparation method thereof
CN113475620A